EU Foreign Policy and Global Security : Instrument contributing to Stability and Peace (IcSP) - Kurnikova, Vasilisa; Votoupalová, Markéta; Kristek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The main goal of this work is to determine the degree of effectiveness of the EU’s activities aimed at resolving crisis situations in the world, to determine the degree of EU involvement in the prevention of global conflicts, peacebuilding and the activities of the Union in general. Preparedness for crises in various regions of the world. The work plans to study the principles and tools of the EU to counter and prevent global and trans-regional threats. The main tool under study in the work is The Instrument contributing to Stability and Peace (IcSP), which is at the present stage the most relevant and, according to preliminary estimates, the most effective option for the EU’s influence on stability and well-being in the world. The work pays special attention to the study, econometric analysis and quantitative assessment of the success of using IcSP in practice during the study period 2013-2021, designated by the research regulations based on the beginning of the use of the tool under study and its current relevance. The work examined the main difficulties that arise when implementing IcSP in various regions of the world, including with regard to the applicability of the tool based on the nature of ruling regimes, the readiness of government entities to reform ineffective principles of leadership, cultural and national characteristics, as well as the readiness of representatives of regions of the world to counteract crisis situations with the help of advanced financial support mechanisms. The statistics of financing of numerous projects of various directions implemented by the EU using the IcSP tool were studied, which made it possible to form an empirical basis for quantitative assessment and econometric analysis of the effectiveness of IcSP.
The result of the study is a review of the collected empirical data, an interpretation of complex correlation analysis of statistics and a conclusion about the degree of statistical significance of the use of IcSP for increasing preparedness for crises, increasing the ability to counteract crises, as well as for the effectiveness of their resolution, revealed as a result of constructing an OLS multiple regression model.
Vedoucí práce: Markéta Votoupalová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses